2022
DOI: 10.1109/tcst.2021.3118296
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Irrigation Allocation for Large-Scale Arable Farming

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The LSTM is a unique kind of neural network that is particularly useful for time series analysis. Furthermore, the customers' watering needs for the crops can be predicted by the collected models [25]. To increase watersaving efficiency, the data fusion models consider real-time sensor data, weather forecasts, irrigation records, and past local weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The LSTM is a unique kind of neural network that is particularly useful for time series analysis. Furthermore, the customers' watering needs for the crops can be predicted by the collected models [25]. To increase watersaving efficiency, the data fusion models consider real-time sensor data, weather forecasts, irrigation records, and past local weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jim'enez et al [9] used the agronomic standards of each crop, such as crop coefficient, root depth, and soil water balance to evaluate the degrees of water wastage; a top-k query was then applied to select the solution with the least wastage. Cobbenhagen et al [10] employed various crop-growth models to estimate total crop profit and found the solutions with the most profit using top-k. More recently, Zhang et al [11] used the agronomic standards of the crops, soil water, and salt balance limits to construct a two-layer multi-objective agricultural water allocation model, which evaluates economic benefits and irrigation water productivity. Solutions were also obtained in this case using a top-k query.…”
Section: Introductionmentioning
confidence: 99%